In Vitro Study of Netilmicin Compared with Other Aminoglycosides - Fu, Kwung P. (1976)
Netilmicin (Sch 20569) is an ethyl derivative of gentamicin C(1a) that is active against most Enterobacteriaceae, Pseudomonas aeruginosa, and Staphylococcus aureus isolates. Among 342 clinical isolates tested, all staphylococci; 92% of Escherichia coli, 93% of Klebsiella pneumoniae, and 92% of Enterobacter were inhibited by 0.8 μg or less of netilmicin per ml, but only 78% of P. aeruginosa were inhibited by 3.1 μg or less per ml. Most clinical isolates of enterococci, Serratia marcescens, and Providencia were not inhibited by 3.1 μg of netilmicin per ml. Like other aminoglycosides, the netilmicin in vitro activity was markedly influenced by the growth medium used, with activity decreased by sodium, calcium, and magnesium. Netilmicin was more active at alkaline pH. Addition of magnesium to Pseudomonas or Serratia pretreated with netilmicin produced inhibition of killing. Netilmicin was more active than gentamicin, sisomicin, tobramycin, or amikacin against E. coli and K. pneumoniae. Netilmicin inhibited growth of all gentamicin-resistant isolates of Klebsiella and Citrobacter tested, but only 73% of E. coli; Pseudomonas and Providencia were resistant to netilmicin. Most Serratia (95%) and indole-positive Proteus (83%) isolates were resistant to netilmicin but were inhibited by amikacin.